Effective retransmission in network coding for TCP - Jing CHEN; Xue-peng SONG; Fang LIU (Tongxin xuebao)
Theoretical analysis for evaluating the decoding delay and redundancy of the different retransmission schemes show that the feedback based retransmission scheme has a lower decoding delay than the scheme with a fixed retransmis-sion rate, whereas these schemes which retransmit packets containing all packets in the coding window are deeply influ-enced by the loss rate. Therefore a novel network coding retransmission scheme which uses the implicit information of seen scheme to acquire the number of packets the receiver needs for decoding packets is proposed, the encoding rules of retransmission to let a part of packets decodable in advance are changed. Proposed scheme can work well on handling not only random losses but bursty losses in reducing decoding delay. More important, it isn't influenced by the loss rate, and thus can effectively mask losses. Simulation results show that the new scheme significantly outperforms the previous coding approach in reducing decoding delay and increasing throughput at the same time. It is more possible to be imple-mented in practical systems.